2016
DOI: 10.1038/srep19967
|View full text |Cite
|
Sign up to set email alerts
|

Direct flow cytometry measurements reveal a fine-tuning of symbiotic cell dynamics according to the host developmental needs in aphid symbiosis

Abstract: Endosymbiotic associations constitute a driving force in the ecological and evolutionary diversification of metazoan organisms. Little is known about whether and how symbiotic cells are coordinated according to host physiology. Here, we use the nutritional symbiosis between the insect pest, Acyrthosiphon pisum, and its obligate symbiont, Buchnera aphidicola, as a model system. We have developed a novel approach for unculturable bacteria, based on flow cytometry, and used this method to estimate the absolute nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
87
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(105 citation statements)
references
References 56 publications
10
87
2
1
Order By: Relevance
“…6). In prior studies (29,40), Buchnera copy number increased during aphid development into early adulthood; however, we observed consistent decreases across all experimental lines in middle-instar nymphs. The reason for this is unclear but may involve stage-specific amplification inhibitors.…”
Section: Figmentioning
confidence: 43%
“…6). In prior studies (29,40), Buchnera copy number increased during aphid development into early adulthood; however, we observed consistent decreases across all experimental lines in middle-instar nymphs. The reason for this is unclear but may involve stage-specific amplification inhibitors.…”
Section: Figmentioning
confidence: 43%
“…Potentially, the correlation could reflect differences in compartmentalization of Buchnera between maternal and embryonic bacteriocytes, which might vary with aphid growth rate, thus impacting the ratio of Buchnera to aphid genomes. Weighing against this explanation are the results of Simonet et al (28), who found that only a small proportion of the Buchnera cells within a fourth-instar A. pisum (the stage we measured) are within the embryos. Nonetheless, explanations such as these, in which the aphid genotype has independent effects on Buchnera titer and on fecundity, cannot be ruled out as possible explanations for the correlation.…”
Section: Discussionmentioning
confidence: 59%
“…A recent study (28) highlighted the cellular dynamics of Buchnera across the A. pisum life cycle using Buchnera cell counts rather than Buchnera genomic copy number, as in our experiments. It is likely that cell numbers and genomic copy numbers are strongly correlated; and it is not clear which is a better indicator of functional capacity of symbionts within a host individual.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Simonet et al . () suggested that the rapid increase of both Buchnera and bacteriocyte number during nymphal development was linked to the insect's high nutritional demands: as the insect grows, molts, and develops embryos, its nutritional needs increase.…”
Section: Aphidsmentioning
confidence: 99%